A finite-difference thermal model of a three-phase coreless linear motor as a heat source. (5th August 2015) - Chow, J.H.; Zhong, Z.W.; Lin, W.; Khoo, L.P.; Kiew, C.M.
Abstract: The deformation in the carriage of a linear motor stage is due to the temperature gradient, and it affects the accuracy in precision machines. This is largely due to indeterminist temperature variations in the materials caused by the nonlinearity of heat transfer phenomena. The main heat source of a linear motor actuated stage is the motor coil. The motor coil is supplied by a three-phase current input for actuation. The part of power that goes to the motor coil results in a joule heating effect. With joule heating as the heat input, and heat losses through effective convection, the temperature variation in the carriage of the motor increases. A three-dimensional finite difference method is adopted to model the motor coil to calculate the amount of the heat transferred to the carriage. The theoretical results are verified with experiments. It is demonstrated that the proposed model is capable to predict accurately the temperature variation at the interface between the motor coil and carriage, and therefore the heat flux can be obtained for the full range of the motor operating power. Highlights: The characteristic of linear motor as a heat source is investigated. A finite difference thermal model was formulated in state space. The correlation between current input and heat produce has been developed. The verification of the model with different loading was done.